Tratamiento anticoagulante oral en pacientes con fibrilación auricular no valvular - Arrojo Arias, E. (Aten Primaria, 2002)
OBJECTIVES: To evaluate the knowledge, attitudes and difficulties of family doctors in the indication of oral anti-coagulation treatment (OCT) in patients with nonvalvular auricular fibrillation (NVAF). DESIGN: Transversal descriptive study. SETTING: Area 11 of Madrid primary care PARTICIPANTS: 250 doctors by simple randomised sampling. Main measurements. After a pilot study at a health centre, mailing of a questionnaire with a subsequent re-mailing. This collected social and personal details, knowledge of the question, attitudes and difficulties. RESULTS: 157 (62.8%) replied; 91 were women (58.0%); mean age was 39 (SD, 6.0). 97 had reviewed the question recently (61.8%). 110 thought that the anti-aggregation criteria were clear (70.1%; CI, 62.2–77.0%), 107 that the oral anticoagulation criteria were (68.2%; CI, 60.2–75.2%), 132 that the OCT risks were (84.1%; CI, 77.2–89.2%), and 74 that risk factors of cerebrovascular accident were clear (47.1%; CI, 39.2–55.2%). Initially 96 doctors gave anti-aggregants and referred to cardiology (61.1%; CI, 53.0–68.7%), and 29 began OCT (18.5%; CI, 12.9–25.6%). 134 thought that we avoided initiating OCT (85.3%; CI, 78.6–90.3%), giving as the main reasons the difficulty of monitoring and of requesting further tests, the risks involved and OCT not being up-to-date. Conclusions. Most professionals have the criteria for OCT in NVAF clear, although they continue to avoid the initiation of OCT. The majority approach is to give anti-aggregants and refer to Cardiology, given the risk of the therapy and the difficulties involved in monitoring and requesting further tests.